Pengaruh Video Animasi terhadap Pemahaman Penulisan Tanda Baca dan Huruf Kapital pada Keterampilan Menulis Kelas 4 - Azzahra Nur Salsabilla; Afakhrul Masub Bakhtiar; Ismail Marzuki (Journal Innovation In Education, 2025)
This study aims to determine the effect of animated videos on the understanding of punctuation and capitalization in the writing skills of 4th grade students of MI ASSA'ADAH Bungah in the 2024/2025 academic year. The method used in this study is a quasi-experimental with a Non-Equivalent Control Group design. The research sample consisted of two groups, namely the experimental group that was given treatment in the form of animated videos and the control group that was not given treatment. The instrument used in this study was a test whose validity and reliability had been tested. Based on the results of the data analysis that had been carried out, there was a significant difference between the experimental group and the control group. This was evidenced by the results of the normality test which showed that the experimental group had a significant value greater than 0.05. Thus, it can be concluded that the use of animated videos has a positive effect on the understanding of punctuation and capitalization in the writing skills of 4th grade students of MI ASSA'ADAH Bungah. The results of this study provide an important contribution to the development of more effective learning methods, especially in teaching punctuation and capitalization. Animated videos as a learning medium can be an interesting and interactive alternative to improve students' understanding of aspects of grammar that are often considered difficult. With dynamic visualizations, students can more easily grasp the concepts of punctuation and capitalization, ultimately improving their writing skills. Furthermore, this study also opens up opportunities for further research into the effectiveness of animation media in learning various other aspects of language.